2014
DOI: 10.5498/wjp.v4.i4.133
|View full text |Cite
|
Sign up to set email alerts
|

Racial disparities in psychotic disorder diagnosis: A review of empirical literature

Abstract: Psychotic disorder diagnoses are common in the United States and internationally. However, racial disparities in rates of psychotic disorder diagnoses have been reported across time and mental health professions. This literature review provides an updated and comprehensive summary of empirical research on race and diagnosis of psychotic disorders spanning a 24-year period. Findings reveal a clear and pervasive pattern wherein African American/Black consumers show a rate of on average three to four higher than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
162
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 330 publications
(194 citation statements)
references
References 25 publications
15
162
1
1
Order By: Relevance
“…The majority of psychotic events were directly attributed to SLE, had a tendency to occur early in the course of the disease, and were more frequent in male patients. Psychosis was also more frequent in patients of African ancestry, as is also the case for non‐SLE patients with the same race/ethnicity . The outcome of lupus psychosis, as determined by both physicians and patients, was positive and emphasizes the importance of diagnosing and treating this rare manifestation of NPSLE.…”
Section: Discussionmentioning
confidence: 68%
“…The majority of psychotic events were directly attributed to SLE, had a tendency to occur early in the course of the disease, and were more frequent in male patients. Psychosis was also more frequent in patients of African ancestry, as is also the case for non‐SLE patients with the same race/ethnicity . The outcome of lupus psychosis, as determined by both physicians and patients, was positive and emphasizes the importance of diagnosing and treating this rare manifestation of NPSLE.…”
Section: Discussionmentioning
confidence: 68%
“…Thus, it is thought that ketamine would not be appropriate as a treatment option for patients with schizophrenia and schizoaffective disorder [4]. However, considering the controversy over the diagnosis of schizoaffective disorder and the over diagnosing of mood disorders with psychotic features, especially in African American population [8][9][10][11], it may be worthwhile to explore the feasibility of ketamine as a treatment option for severe depression in these patients, possibly as a last resort.…”
Section: Discussionmentioning
confidence: 99%
“…The challenge is even greater for African Americans and women [8]. It is known that psychotic disorders are over diagnosed in African American populations [10,11]. Moreover, in a study of a Danish population of over 2 million, Laursen et al reported that the chance of a bipolar woman being admitted with the diagnosis of schizoaffective disorder was 103 times higher than the general population of the same age [8].…”
Section: Discussionmentioning
confidence: 99%
“…Another piece of evidence suggesting the depression/ schizophrenia continuum comes from population studies. African-Americans have higher rates of schizophrenia (Schwartz and Blankenship 2014) than the general population yet have decreased rates of depression (Dunlop et al, 2003). Thus their mental health is "frame-shifted" with respect to the Western component of the population.…”
Section: Introductionmentioning
confidence: 99%